Stigmatization and Dishonesty: How Doctors Communicate and Cope with Mental Issues among COVID-19 Patients in Indonesia - Assegaff, Syafiq Basri; Dhani, Rendro; Hollingsworth, Mary Ann; Rinaldi, Enrico Adhitya; Atas Asri, Sri Dhuny (European Scientific Journal, ESJ, 2022)
Background: The coronavirus (COVID-19) outbreak has caused public fear alongside social stigma and discrimination. As a result, people hide the illness to avoid discrimination. This study focuses on investigating doctor-patient communication, their challenges when diagnosing suspected COVID-19 patients, and how the physicians communicated with patients’ mental issues. Methods: A mixed-methods approach examined this phenomenon and an online survey was conducted among 221 Indonesian doctors. The following were quantitatively examined: theme of Covid stigma and patient openness, patient/physician interaction and communication, and information and stigmatization of Covid. Qualitatively, two Focus Group Discussions (FGD) were conducted with five physicians and four COVID-19 survivors or their family members. Thereafter, interviews were set up with the selected four persons. Results: 74.2% of respondents encountered patients with lack of honesty or openness, while 55% of physicians claimed that 1-2 patients out of every 10 patients covered up about their illness. 27% of physicians indicated that 3-5 of 10 patients did not tell the truth. Majority of respondents opined that the media/social media played a large role in the promotion of stigma for those who had COVID-19. Conclusion: Study results affirmed belief in a link between the stigma of COVID-19 and patients’ dishonesty. Results indicated that many individuals are reluctant to disclose their true positions for fear of stigmatization by the people around them. This is linked to the stigma of COVID-19 and patient reluctance to be honest about their health/illness per impact of COVID-19. This research concluded that doctors need to find creative ways to communicate with their patients so as to increase patient honesty about illness.